Factors associated with the homicide profile of a prison population: Analysis of the Peruvian national census, 2016 - Nadia Castillo-Caciano; Fabriccio J. Visconti-Lopez; Rodrigo Vargas-Fernández (Cogent Psychology, 2022)
To determine the factors associated with the homicide profile of the prison population in Peru. A cross-sectional analytical study was conducted on the data of inmates surveyed in the First National Prison Population Census of 2016. The dependent variable was committing intentional homicide which was constructed from the Peruvian Penal Code and the International Classification of Crime for statistical purposes. To determine the factors associated with the homicide profile, a generalized linear model of the Poisson family with logarithmic link function was used and crude and adjusted prevalence ratios were estimated. A total of 57,866 inmates were included, of whom 6.60% had committed intentional homicide. In addition, some sociodemographic, mental health, social and family environments, and crime characteristics we found to increase the probability of inmates committing intentional homicide. Almost 7 out of 100 inmates committed intentional homicide. Although our findings are based on a prison population, the associated factors reported in our study could be useful for the implementation of strategies to reduce the homicide rate in Peru and for judicial decision-making.